Determination of Flow Patterns Occurring at the Downstream of a Tilting Flume Channel Gate with 3 Variations of Inclination Angles. - Irianto, Djoni; Ulhaq, Naufal Dhiya (Engineering And Technology Journal, 2024)
Flow that occurs in the tilting flume channel often changes when observed. This phenomenon is closely related to the variation in the channel’s bottom angle as it crosses the open channel, resulting from water input supply or water supply from reservoirs pumped by water researchers. The flow of water through the open channel is influenced by the presence of the channel’s bottom surface profile and various angles. When a certain discharge is given, visible flow patterns can be observed on the water surface, while the unseen flow above the water surface is referred to as the Energy Gride Line (EGL). If the energy that occurs in the channel is not measured, it may lead to water jumping. The structured water jump can be observed to understand the flow patterns that occur. To avoid undetected flow patterns, hydraulic structures are required, one of which is a water gate with an opening below, commonly known as a Sluice Gate. This water gate is easily operable, either manually or with the availability of excess water supply. Calculating the operational water requirements can be challenging due to the influence of the depth and jumps occurring downstream of the gate. Often, the hydraulic jump’s differences tend to overlook these measurements, which can become a hindrance when there is an excess water supply during peak flow conditions. To address this issue, it is necessary to conduct a model test using an instrument known as the Sluice Gate, which generates hydraulic jumps. This area of research needs further exploration in the laboratory. The Sluice Gate model in the equipment is equipped with instruments, various gate openings, and adjustable pressurized water gates with measurable flow rates. To analyze the jump height, flow patterns, and velocity using a flow watch measuring instrument, the researchers conducted tests with three specific gate openings, testing and measuring the depths (Y) at different positions of the channel’s bottom slope. The test started with gate openings of 0.5, 0.75, and 1.00, reading the instrument, moving the gate positions from a depth of 2 cm to the highest depth of 5 cm. Graphing the test results of the Sluice Gate apparatus, which is a sliding gate-type apparatus manually operated, the researchers conducted three tests for each gate opening with pumping, recording, and mapping the depth values, jump lengths, and travel times from the instrument on the testing apparatus. The subsequent recommendation of the Sluice Gate test analysis is intended to provide information for water construction planning, indicating that the test results with various slopes under certain conditions have different depth values and jump times (t). Furthermore, the researchers determine the positioning of the model gate, which can be used to determine the water depth (Y) after jumping (cm). This laboratory research involves a channel model. The objective of this study is to publish a journal article presenting the simulation results determining the flow patterns occurring in the channel with three different bottom slope angles (5°, 15°, 25°). The results will be presented in tables and graphs and then documented in an article submitted to an international journal.